#
Is there formal proof for (-)(-)= (+). Please help me to get the answer. This, has been ask by my Maths teacher in school.

A expert answered this, but, he told me that how (-1) x (-1) = 1. Actually, it has some expressions like "-(-1) = 1.

Here we have (-)(-).. without proof.

So, please be a little specific.

Hi,

First of all the axioms does not require proof because they are self evidently true.

and the previous answer:

From the distributive law of multiplication we have

a*(b+c) = a*b + a*c

which holds for all real numbers. So it will hold if we put a=-1, b=1 and c=-1

(-1)*(1+(-1)) = (-1)*1 + (-1)*(-1)

1+(-1) = 0 and -1*1 = -1 so we get

(-1)*0 = -1 + (-1)*(-1)

0 = -1 + (-1)*(-1)

rearrange to get

1 = (-1)*(-1)

It is correct and also

The above explanation has nowhere "-(-1) " so it is the required proof.

**
**